Childhood cancer presentation and initial outcomes in Ethiopia: Findings from a recently opened pediatric oncology unit. - Diriba Fufa Hordofa; Muktar Ahmed; Zewdie Birhanu; Sheila Weitzman; Julie Broas; Aziza Shad; Miguel Bonilla; Thomas B Alexander (Public Library of Science (PLoS), 2024)
There were no pediatric oncology centers in southwest Ethiopia prior to 2016. This study aims to describe presenting diagnoses and initial outcomes at Jimma University Medical Center (JUMC), the first pediatric oncology unit (POU) in southwest Ethiopia, provide initial insights into regional pediatric cancer epidemiology, illustrate the rapid growth of pediatric cancer services, and highlight ongoing challenges. We used a retrospective descriptive approach to assess the epidemiologic pattern and initial treatment outcomes of pediatric cancer at JUMC POU from August 2016 through December 2022. During the study period, 749 children were diagnosed with cancer at JUMC. The mean age was 7.2 years (20 days-18 years). Acute lymphoblastic leukemia was the most common diagnosis (16.4%), followed by non-Hodgkin lymphoma (12.4%), Wilms tumor (11.1%), soft tissue sarcoma (8.8%), Hodgkin lymphoma (8.4%), and retinoblastoma (8.3%). Brain tumors accounted for only 2.7% of the diagnoses. Of the 703 patients that were not referred elsewhere, 42% of the patients abandoned treatment, 29% died, 17% completed treatment, and 7% remained on treatment at the time of this assessment. The findings emphasize the growth in the diagnosis and treatment of children with cancer in the southwest region of Ethiopia. The data suggests a different epidemiologic profile of childhood cancer cases diagnosed at the JUMC POU compared to high-income countries and neighbouring countries in Africa. Treatment abandonment remains a barrier to care. Ongoing areas of focus include establishment of a hospital-based cancer registry, reduction of treatment abandonment, improvement of diagnostic capacity, and increased access to advanced supportive care.